Transparency Of Village Development Planning Deliberations (Musrenbangdesa) As A Policy Direction - Tardi Setiabudi (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2024)
The Village Development Planning Deliberation (Musrenbangdesa) in Kandangsapi Village, Cijaku District, Lebak Regency has been carried out properly. This research is important to find out how the role of Village Governments and Village Institutions as policy makers when carrying out their duties, namely realizing transparent development planning deliberations to village communities. This research uses a descriptive qualitative approach method by observation, interviews and data in the field. While technical analysis uses data triangulation, which is collecting data from various sources and then digging for a truth. In the implementation of Musrenbangdesa there is less transparency, policy direction is less disciplined, and priority programs are not based on research studies. In addition, it is more about the interests of the group so that the programs that run are less optimally felt by the community, especially in the field of empowerment and development of rural communities.